A multi-parameter approach to measurement of spontaneous myogenic contractions in human stomach: Utilization to assess potential modulators of myogenic contractions. (June 2022) - Straface, Marilisa; Kouassi, Marie-Ange; Makwana, Raj; Crawley, Ellie; Palmer, Alexandra; Cai, Weigang; Gharibans, Armen; Adebibe, Miriam; Loy, John; O'Grady, Greg; Andrews, Paul LR; Sanger, Gareth J.
Abstract: Electrical slow waves, generated by interstitial cells of Cajal (ICC), cause spontaneous contractions of human stomach. Software was developed to measure muscle tone and eleven different parameters defining these contractions in human stomach, displaying data as radar plots. A pilot study assessed the effects of potential modulators, selected from among compounds known to influence ICC activity; n = 4–7 each concentration tested/compound. Human distal stomach (corpus-antrum) muscle strips were suspended in tissue baths for measuring myogenic (non-neuronal) contractions in the presence of tetrodotoxin (10 -6 M). Initial characterization: Contractions (amplitude 4 ± 0.4mN, frequency 3 ± 0.1 min -1, n = 49) were unchanged by ꭃ-conotoxin GVIA (10 -7 M) or indomethacin (10 -6 M) but abolished by nifedipine (10 -4 M). Carbachol (10 -7 M) increased contraction rate and amplitude; 10 -6 -10 -5 M increased tone and caused large, irregular contractions. [Ca 2+ ] i modulators : Ryanodine (10 -5 -10 -4 M) increased muscle tone accompanied by inhibition of myogenic contractions. Xestospongin-C (10 -6 M; IP3 channel inhibitor) had no effects. SERCA pump inhibitors, 2-APB and cycloplazonic acid (10 -5 -10 -4 M) increased tone and myogenic contraction amplitude before abolishing contractions; thapsigargin was weakly active. CaCC blockers : MONNA and CaCCinh-A01 had little-or-no effects on tone but reduced myogenic contractions; MONNA (10 -4 M) was more effective, reducing amplitude (77.8 ± 15.2%) and frequency. Ca V 3.1/3.2/3.3 channel block : Mibefradil reduced tone and myogenic contraction amplitude ( p IC50 4.8 ± 0.9). Inward-rectifying K + -channel inhibitor : E-4031 (10 -4 M) increased contraction duration (17.4 ± 5.8%). Conclusions: (1) Measurement of multiple parameters of myogenic contractions identified subtle differences between compounds, (2) only E-4031 and CaCC blockers influenced myogenic contractions, not muscle tone, (3) studies are needed with compounds with known and/or improved selectivity/potency for human targets affecting ICC functions. Graphical Abstract: ga1 Highlights: Myogenic contractions of human stomach at frequency of slow wave activity in vivo. CaCC blockers reduced contraction amplitude and frequency. The inward-rectifying K + -channel inhibitor E-4031 increased contraction duration. No other modulator of interstitial cells of Cajal affected only the contractions. The efficacy, potency, selectivity of the compounds at human targets are unclear.